PEMBUATAN ARANG DAN BRIKET ARANG DARI KA YU MANIS (Cinnamomum burmanii Ness ex. BL) DAN KAYU .SUKUN - Sri Komarayati; Gusmailina Gusmailina (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
The aim of this experiment is to find the properties of cassiavera and, breadfruit charcoal and charcoal briquette.The kiln used was the typical size of 200 liter oil drum with specie L design incorporating 12 holes of 13 mm in diameter at different elevations. The kiln also had a short chimney of 30 cm high at the top with 10 cm in diameter. The result showed that charcoal yield were 24.74 % for cassiavera and 23.01 % for breadfruit. Volatile matter was 18.61 %, fixed carbon was 78.31 % and calorific value was 7035.03 cal/g for cassiavera charcoal and volatile matter was 14.27 %, fixed carbon was 73.10 % and calorific value was 6320.12 cal/g for breadfruit charcoalThe moisture content of charcoal briquette ranges from 8.41 to 5. 92 % ash content from 4. 65 to 5. 03 % , volatile matter from 28.87 to 29.48 %, fixed carbon from 65.87 to 66.10 %, density from O.11 to 0.64 g/cm3, compressing strength from 275 to 450 kg/cm2 and the calorific value from 5684. 59 to 6792.58 cal/g.Based on the physical and chemical properties, cassia-vera and breadfruit charcoal briquette can be used as sources of energy.